Tuberous sclerosis complex: neonatal deaths in three of four children of consanguineous, non-expressing parents. Issue 3 (March 1997) - Ruggieri, M; Carbonara, C; Magro, G; Migone, N; Grasso, S; Tinè, A; Pavone, L; Gomez, M R
Abstract : We describe here four sibs, born to consanguineous, healthy, asymptomatic parents. Three of these infants had a rapidly fatal course in the neonatal period; death was attributed to congestive heart failure with radiographic evidence of cardiomegaly in all of them. Necropsy was done in only one of them and showed the typical findings of tuberous sclerosis complex (TSC) in the central nervous system (CNS), kidneys, heart, and liver. The fourth sib, currently 2 years old, also has typical signs of TSC, namely hypomelanotic skin macules and calcified subependymal nodules. Both parents and a living maternal grandmother had appropriate examination, which included skin inspection under Wood's lamp, dental examination, fundoscopy, echocardiography, abdominal and renal ultrasound, and head CT and MRI scans, and no signs of TSC were found in either parent or in the only living grandmother. By history alone there is no other relative with signs or symptoms suggestive of TSC. Linkage analysis and loss of heterozygosity (LOH) investigations on a variety of lesions obtained from postmortem and tissue or blood specimens from all available family members studied failed to identify a microdeletion in the chromosomal regions where TSC genes are located. It is very unusual that in a single TSC family there were three consecutive neonatal deaths, and very likely that all had cardiac rhabdomyomas. Moreover, to the best of our knowledge, there are no previous reports of TSC families with more than one affected sib, unusually severe manifestations of the disease, and completely normal, consanguineous parents.